An empirical study of the impacts of parameters in micro electrochemical drilling of Al 7075 alloy composites with SiC and fly-ash. (2023) - Swamy Chinamilli, N.V.S.; Azhagarsamy, P.; Antony Prabhu, D.; Rajesh, S.; Lokesh Kumar, P.J.; Selvan, T.A.; Viswanathan, A.; Madhankumar, S.
Abstract: The Electrochemical Drilling Technique (EDT) is utilized to bore metal alloys into the desired geometric forms. The present study investigates that various typical electrochemical drilling process variables, line supply-voltage (VT), electrolytic solution (ES), and pulse-on time (PT), impact the output responses namely material extraction rate as well as surface-roughness of stir cast Al7075 alloy, SiC, and fly-ash powder mixtures. These aluminum-matrix composites could be used to construct bridges, frames, and containers that will store pollutants, dairy, as well as other corrosive compounds; they can also be used to replace stainless steel, which is used in salty areas to avoid corrosion. Taguchi's experimental design is utilized in this study to investigate the effects of every input parameter on the Material-Extraction Rate (MER) and surface-roughness. Also, the significance of each parameter has been identified using an analysis of variance.